Combined effect of acidic beverages and immersion time on bonding strength of composite to enamel: an in-vitro study - Mahdan, Mohd Haidil Akmal; Abidin, Nur Syahirah; Mohd Zaidi, Nur Ain Athirah; Sulaiman, Ahmad Syahrizan (Sciencedomain International, 2022)
Introduction: Carbonated beverages are widely consumed over the world. The effect of acidic liquids on dental enamel has a significant impact on composite resin adhering to the enamel substrate. The purpose of this study was to see how acidic beverages affected the bonding of composite resin to exposed enamel. Methods and Materials: 128 premolars were taken and divided into four groups for both 24 hours immersion (n=40) and 15 days immersion (n=40). The samples were divided into the following categories: G1: 3x/15 mins immersion in Beverage A, G2: 3x/15 mins immersion in Beverage B, G3: 3x/15 mins immersion in Beverage C, G4: 3x/15 mins immersion in artificial saliva as control group. Prior to immersion, the buccal surfaces of the enamel were minimally ground at the layer of enamel solely using a Tungsten carbide bur, then flattened with #600 - #1200 silicon carbide paper (SiC) paper. Specimens were submerged in the media for 24 hours and 15 days, respectively. Following immersion, the specimens’ prepared surfaces were repaired using composite resin. The enamel pattern was morphological analyzed using a Scanning Electron Microscope (SEM) and the shear bond strength was determined . Results: One-way ANOVA with multiple comparison tests was used to statistically evaluate the data. When compared to control media, all of the beverages tested significantly reduced shear strength. Following immersion in the test beverages, enamel's morphology changed noticeably, with Beverage A group displaying the most pronounced morphological changes. Conclusion: All acidic beverages examined had a detrimental impact on shear strength. In different periods of time, varied degrees of enamel demineralization were detected.